2010
DOI: 10.1007/s10862-010-9181-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Score Dependability of the Wisconsin Schizotypy Scales Using Generalizability Analysis

Abstract: To investigate the reliability of the Wisconsin Schizotypy Scales, this study applied generalizability analysis with two college student samples who completed the scales at two time points. The results indicated that the Revised Social Anhedonia Scale had acceptable levels of score dependability, but that the score dependability for the other scales (the Physical Anhedonia Scale, the Perceptual Aberration Scale, and the Magical Ideation Scale) was below an acceptable level of .80. The patterns of variance comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
(23 reference statements)
2
20
0
2
Order By: Relevance
“…They consisted of the following items from the original scales: Magical Ideation Scale (items 1,2,5,6,9,12,13,21,22,23,24,25,26,27,29), Perceptual Aberration Scale (items 8, 10, 11, 13, 16, 19, 21, 23, 24, 25, 26, 27, 29, 30, 31), Revised Social Anhedonia Scale (items 1,3,4,7,10,13,14,17,19,21,26,30,31,35,37), and Physical Anhedonia Scale (items 3, 10, 15, 19, 24, 29, 35, 36, 39, 42, 45, 46, 47, 54, 60). Unlike the participants in our prior studies ( [Winterstein et al, 2010] and [Winterstein et al, in press]), the participants in this sample completed only the 60 items from the four short forms. To evaluate the validity of the short forms' scores, we measured many additional constructs.…”
Section: Procedures and Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…They consisted of the following items from the original scales: Magical Ideation Scale (items 1,2,5,6,9,12,13,21,22,23,24,25,26,27,29), Perceptual Aberration Scale (items 8, 10, 11, 13, 16, 19, 21, 23, 24, 25, 26, 27, 29, 30, 31), Revised Social Anhedonia Scale (items 1,3,4,7,10,13,14,17,19,21,26,30,31,35,37), and Physical Anhedonia Scale (items 3, 10, 15, 19, 24, 29, 35, 36, 39, 42, 45, 46, 47, 54, 60). Unlike the participants in our prior studies ( [Winterstein et al, 2010] and [Winterstein et al, in press]), the participants in this sample completed only the 60 items from the four short forms. To evaluate the validity of the short forms' scores, we measured many additional constructs.…”
Section: Procedures and Scalesmentioning
confidence: 99%
“…In addition to their wide use in cross-sectional studies, the Wisconsin Schizotypy Scales have been used successfully in several longitudinal studies of the development of schizophrenia-spectrum disorders (e.g., [Chapman et al, 1994], [Gooding et al, 2005], [Gooding et al, 2007] and [Kwapil, 1998]). Because of the popularity of the Wisconsin Schizotypy Scales, recent work has examined their psychometric properties employing current measurement models ( [Winterstein et al, in press] and [Winterstein et al, 2010]). The scales were originally developed using classical test theory.…”
Section: Introductionmentioning
confidence: 99%
“…The psychometric properties of the WSS within the CTT framework have been described in the original source articles and in subsequent reviews (e.g., Kwapil et al 2002Kwapil et al , 2008. In brief, research has found good evidence for internal consistency, such as internal-consistency coefficients ranging from .79 to .91 (Winterstein et al 2010). In a study of temporal stability, test-retest reliability coefficients (across a period of 2 to 3 months) ranged from .63 to .81, and subsequent generalizability analyses showed that time explained minimal variance (less than 1%) in WSS scores (Winterstein et al 2010).…”
Section: Psychometric Assessment Of Schizotypymentioning
confidence: 99%
“…In brief, research has found good evidence for internal consistency, such as internal-consistency coefficients ranging from .79 to .91 (Winterstein et al 2010). In a study of temporal stability, test-retest reliability coefficients (across a period of 2 to 3 months) ranged from .63 to .81, and subsequent generalizability analyses showed that time explained minimal variance (less than 1%) in WSS scores (Winterstein et al 2010). Confirmatory factor analyses have provided evidence for the scales' structural validity, particularly the division of the scales into broader positive and negative symptom dimensions (Kwapil et al 2008).…”
Section: Psychometric Assessment Of Schizotypymentioning
confidence: 99%
See 1 more Smart Citation